Filsafat Rasionalisme Sebagai Dasar Ilmu Pengetahuan - Meisakh Nur Anugrah; Usman Radiana (Jurnal Filsafat Indonesia, 2022)
Philosophy of rationalism is an understanding in philosophy that says the most important tool forobtaining and disseminating knowledge is reason or reason. Rationalism believes that the way toachieve knowledge is to rely on logic and intellect. This study aims to look at the philosophy thatis the basis of the formation of science. The research approach that researchers use in writingscientific papers is a type of library research. Humans use their minds to capture and findknowledge. The flow of rationalism believes that truth exists in human reason and cannot bebased on a lie, because reason is a creation of God given to humans and there is no possibilityof a lie. Rationalism is something that makes reason or reason the source of all knowledge, whichis obtained by the way we think. This is what became the basis or initially emerged science andin the and there is science that emerges from the results of the philosophy of rationalism that wecan feel until now, such as mathematics which is all accepted as absolute truth so that it can beconcluded that the philosophy of rationalism is a basis of truth. which focuses on reason or theratio that creates knowledge.